2021
DOI: 10.1002/ajh.26307
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the human ABO genotypes and their association to common inflammatory and cardiovascular diseases in the UK Biobank

Abstract: The ABO gene contains three major alleles that encodes different antigens; A, B, and O, which determine an individual's blood group. Previous studies have primarily focused on identifying associations between ABO blood groups and diseases risk. Here, we sought to test for association between ABO genotypes (OO, OA, AA; OB, BB, and AB) and a large set of common inflammatory and cardiovascular diseases in UK Biobank as well as disease‐related protein biomarkers in NSPHS. We first tested for association by conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…Moreover, a couple of studies related to the ABO phenotype present links between genetically determined human ABO blood groups with increased risk of various infectious diseases [ 27 ]. The molecular level of ABO blood groups and their association with various diseases should be evaluated, too [ 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a couple of studies related to the ABO phenotype present links between genetically determined human ABO blood groups with increased risk of various infectious diseases [ 27 ]. The molecular level of ABO blood groups and their association with various diseases should be evaluated, too [ 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, J. Höglund et al found 39 plasma proteins were associated with variation at the ABO locus. For example, proteins with functions related to tumorigenesis (CA9, Gal-9, and KLK6) and pro-inflammatory or anti-inflammatory functions (IFN-gamma-R1, IL-18BP, and MARCO) [ 6 ]. Generally, the overexpression of these proteins leads to an abnormal cell proliferation or cell growth.…”
Section: Introductionmentioning
confidence: 99%
“…The United Biobank investigation suggests that the ABO genotypes are strongly associated with common inflammatory and CV diseases. In addition, the ABO blood groups are associated with different levels of VWF and platelet endothelial cell adhesion molecule-1 [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite mounting evidence supporting the critical link between inflammation and AF recurrence, some studies suggest the increased levels of these inflammatory biomarkers simply represent the signs of local inflammation and myocardial injury after catheter ablation and are not as valuable as a predictor of AF recurrence [ 8 ]. Numerous studies demonstrated the association of ABO blood groups with inflammation, thromboembolism, aging diseases, and CV diseases [ 9 ]. Patients with non-O-type blood groups (A, B, or AB type) have a higher risk of thromboembolic events such as coronary artery diseases, cerebrovascular ischemic events, and peripheral vascular disease than those with the O-type blood group [ 10 ].…”
Section: Introductionmentioning
confidence: 99%